Shedding Structured Light on Molecular Immunity: The Past, Present and Future of Immune Cell Super Resolution Microscopy - Johanson, Timothy M.; Keenan, Christine R.; Allan, Rhys S. (Frontiers in Immunology, 2021)
In the two decades since the invention of laser-based super resolution microscopy this family of technologies has revolutionized the way life is viewed and understood. Its unparalleled resolution, speed, and accessibility makes super resolution imaging particularly useful in examining the highly complex and dynamic immune system. Here we introduce the super resolution technologies and studies that have already fundamentally changed our understanding of a number of central immunological processes and highlight other immunological puzzles only addressable in super resolution.